Exploring Junior College Students’ Experience on Using Medium Blogs Integrated Essay Reading and Writing Class - Stellamaris Siana Lusi; Dangin (Jurnal Dunia Pendidikan, 2023)
This study aims to investigate the life experiences of students in using blogging media as a tool for teaching writing in reading and essay writing classes. The respondents were English language students at Mercu Buana University, Yogyakarta, who had been using the blog medium since the third semester. The findings reveal the Strengths, Weaknesses, Opportunities and Threats (SWOT) of the blog medium as a result of students' experience writing blogs using the blog medium in reading and essay writing classes. Medium Blog is seen as a tool that is freely accessible, has a variety of features. In addition, it was discovered that the Medium Blogs contained a defect in the form of a limited number of free accesses, which forced students to maintain information separately or in different storages. Apart from that, the medium blog also displays the works of other writers so that it can become a reference for novice writers.